Change in calculated cardiovascular risk due to guideline revision: A cross-sectional study in the Netherlands - Luymes, Clare H; de Ruijter, Wouter; Poortvliet, Rosalinde KE; Putter, Hein; van Duijn, Huug J; Numans, Mattijs E; Drewes, Yvonne M; Blom, Jeanet W; Assendelft, Willem JJ (The European journal of general practice, 2015)
Background: Guidelines and accompanying risk charts concerning cardiovascular risk management (CVRM) are regularly revised worldwide. Objective: To evaluate whether revision of the Dutch CVRM guideline has led to the reclassification of patients and, accordingly, to changes in drug recommendations. Methods: All medical records (year 2011) of patients aged 40-65 years with no history of cardiovascular disease (CVD) but using antihypertensive and/or lipid-lowering drugs, were selected from the Registration Network of General Practices associated with Leiden University Medical Center. Multiple imputation techniques for missing determinants were used. The individual cardiovascular risk was calculated and the resulting drug recommendation was assessed according to both the 2006 and 2012 versions of the guideline. Results: In total, 2075 patients were selected, of whom 1248 fulfilled the guideline criteria (systolic blood pressure 115-180 mmHg and total cholesterol/high-density-lipoprotein-cholesterol ratio 3.5-8). According to the 2012 guideline, 58.2% of the patients had low risk and 249 patients (20.0%) shifted to a different risk category. For 150 of these patients (12.0%), this category shift implied a shift in drug recommendation. The probability of shifting in drug recommendation increased with increasing age, cholesterol level, and blood pressure, and by being male. Conclusion: Guideline revision may have important implications: based on identical values for risk factors, according to the latest revision of the Dutch CVRM guideline 20% of patients shifted in risk category and 12% of the patients shifted in drug recommendation.